THE METHODOLOGY OF ASSESSMENT OF ECONOMIC EFFICIENCY OF INNOVATIVE PROJECTS WITH VENTURE FINANCING BASED ON REAL OPTIONS METHOD WITH FUZZY SETS ANALYSIS - A. A. Baranov; E. I. Muzyko; V. N. Pavlov (Финансы: теория и практика)
The absence of profi tability is typical for innovative projects on the early stages of its implementation and high risk because of high level of uncertainty of the estimates of forecasted cash fl ows. In this situation, the use of standard methods for economic effi ciency analysis of the projects does not allow to obtain a comprehensive assessment of the advisability of investing, as well as to quantify the accuracy of the dynamics of forecasted indicators. All of this requires the development of the theory and methods for analysis of economic efficiency of innovations and determines the high level of fundamentality of the issue. The application of real options method and fuzzy sets theory is, in our opinion, the directions of the improvement of these methods.The paper deals with the problems of usage of new methods for evaluation of economic efficiency of innovative projects with venture financing in the industry sector. The opportunities of application the real options method to evaluation of the effectiveness of innovative projects with venture financing using fuzzy sets are investigated. Short review of works of foreign and Russian researchers is given.The new methodological approach to the evaluation of the economic effectiveness of innovative projects with venture financing based on the real options method using modified Geske’s formula with fuzzy sets analysis is proposed. The methodological approach will enable to evaluate quantitatively the fact of staged investment of the project and the possibility to stop financing in the case of receiving negative information about its implementation. In other words it will enable to take into account and quantitatively evaluate the flexibility in making managerial decisions.In general, synthesis of the probability methods and fuzzy sets in the analysis of venture financing of innovative projects based on the real options method extends the venture capital investor’s tools used to validate the investment decisions. Also the proposed approach allows to get a more accurate assessment of the effectiveness of investment projects with high degree of uncertainty in comparison with traditional methods.